A two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst and its preparation method and application

By growing BiOBr nanosheets in situ on Bi5Ti3FeO15 nanosheets, a two-dimensional BiOBr/Bi5Ti3FeO15 composite piezoelectric photocatalyst is formed, which solves the problem of insufficient performance of existing piezoelectric photocatalytic materials and achieves a more efficient photocatalytic degradation effect.

CN118751262BActive Publication Date: 2025-04-08JINAN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410964532.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-04-08
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The existing piezoelectric photocatalytic materials have problems with weak piezoelectric polarization charge and serious recombination of photogenerated electrons, resulting in low photocatalytic degradation efficiency.

Method used

Using a two-dimensional BiOBr/Bi5Ti3FeO15 composite piezoelectric photocatalyst, the BiOBr nanosheets are grown in situ on the basis of Bi5Ti3FeO15 nanosheets to form a composite piezoelectric heterojunction with large contact surfaces and interface polarization, improving the overall piezoelectric and photocatalytic performance.

Benefits of technology

The heterojunction interface energy band structure is regulated by the dual-voltage electrodeposited electric field, which promotes photogenerated carrier migration and separation, and improves the photocatalytic degradation efficiency, especially the organic dye degradation performance under light and ultrasound.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118751262B_ABST
    Figure CN118751262B_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst and its preparation method and application; the composite piezoelectric photocatalyst is BiOBr nanosheets on Bi5Ti3FeO 15 Two-dimensional heterojunction nanosheet materials formed by in-situ growth on the basis of nanosheets; two-dimensional Bi5Ti3FeO with ferroelectric-piezoelectric effect synthesized by hydrothermal method 15 The nanosheets were then deposited on Bi5Ti3FeO 15 The BiOBr nanosheets with piezoelectric effect are grown on the surface of the nanosheets. Under the action of light and external ultrasound, the two-dimensional BiOBr / Bi5Ti3FeO 15 The composite photocatalyst can generate a dual piezoelectric electric field, effectively promoting the separation of photogenerated electrons and holes, and achieving efficient piezoelectric-photocatalytic degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite piezoelectric photocatalyst, in particular to a two-dimensional BiOBr / Bi5Ti3FeO 15 The invention discloses a composite piezoelectric photocatalyst, and also relates to a preparation method and application of the composite piezoelectric photocatalyst. Background Art

[0002] With the development of process technology, the environmental pollution problem is becoming more and more serious. Photocatalytic technology using solar energy is green, mild and environmentally friendly, and has broad application prospects in the treatment of environmental pollution. However, due to the light absorption of the photocatalyst itself and the high recombination probability of photogenerated carriers, the efficiency of photocatalytic degradation still needs to be improved. Piezoelectric photocatalysis uses the deformation of piezoelectric materials under the action of external mechanical forces to form a piezoelectric potential. The piezoelectric electric field can effectively promote the separation of photogenerated carriers and couple the water wave energy, wind energy and solar energy in nature. However, single piezoelectric photocatalytic materials also have problems such as weak piezoelectric polarization charge and serious recombination of photogenerated electrons and holes. Therefore, it is urgent to construct an efficient piezoelectric photocatalyst to achieve the best benefits of energy and environment.

[0003] Bi5Ti3FeO 15 It is a typical bismuth layer structure ferroelectric material, four layers [Bi3Ti3FeO 13 ] 2- Sandwiched between two layers [Bi2O2] 2+ In the case of Bi5Ti3FeO, there is spontaneous polarization. 15 The optical band gap is between 1.9 and 2.4 eV, which gives it excellent visible light response. 15 Most of them are based on polycrystalline nanofilms, whose anisotropy makes the ferroelectric / piezoelectric properties still weak, and the preparation method used is the more demanding PLD method. BiOBr is composed of [Bi2O2] 2+The layered structure formed by the staggered layers and double halogen layers along the c-axis direction is a typical piezoelectric material, but the piezoelectric coefficient of BiOBr material is low, which affects its piezoelectric photocatalytic performance. The two piezoelectric materials with different components form an interactive heterojunction material to form a higher polarization, thereby improving the overall piezoelectric performance to a certain extent. The traditional methods for preparing heterostructures mainly include physical mixing and chemical synthesis. The interface effect of the heterostructure prepared by the physical mixing method is relatively weak. If the chemical synthesis method does not form an effective interface, the structural defects formed at the composite interface will become the center of secondary recombination of some photogenerated carriers, thereby weakening the efficiency of the heterojunction in improving the piezoelectric photocatalytic performance. Therefore, how to select suitable materials and use simple methods to construct piezoelectric composite materials that effectively improve piezoelectric photocatalytic performance is an urgent problem to seek solutions. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a two-dimensional BiOBr / Bi5Ti3FeO 15 The invention also provides a composite piezoelectric photocatalyst, a preparation method of the composite piezoelectric photocatalyst and its application in degrading organic pollutants.

[0005] Technical solution: Two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst, BiOBr nanosheets on Bi5Ti3FeO 15 The two-dimensional heterojunction nanosheet material is formed by in-situ growth of nanosheets, in which BiOBr and Bi5Ti3FeO 15 The molar ratio is 3:1 to 1:3.

[0006] The method for preparing the composite piezoelectric photocatalyst comprises the following steps:

[0007] (1) Dissolving a bismuth source, a titanium source and an iron source in water respectively, and stirring to obtain a titanium source solution, an iron source solution and a bismuth source solution; adding the titanium source solution and the iron source solution to the bismuth source solution in sequence, stirring, adjusting the pH to alkaline, stirring, performing a hydrothermal reaction, cooling, centrifuging, washing and drying, and obtaining Bi5Ti3FeO 15 Nanosheets;

[0008] (2) dissolving a bismuth source and a bromine source in water respectively, stirring to obtain a bismuth source solution and a bromine source solution; adding the Bi5Ti3FeO 15 The nanosheets were added to the water and stirred, and the bismuth source solution was added dropwise. After stirring, the bromine source solution was added dropwise. After stirring, the mixture was allowed to stand, centrifuged, washed, and dried to obtain the two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst.

[0009] Wherein, in step (1), the molar ratio of Bi, Ti and Fe in the bismuth source, titanium source and iron source is 5:3:1; the bismuth source is bismuth nitrate or bismuth acetate, the titanium source is tetrabutyl titanate or TiCl4, and the iron source is Fe(NO3)3·9H2O; the concentration of the bismuth source solution, the titanium source solution or the iron source solution is 0.1-0.5 mol / L.

[0010] Wherein, in step (1), an alkaline solution is used to adjust the pH to 10-13, and the alkaline solution is one of NaOH, KOH or ammonia solution, and the concentration is 0.5-2 mol / L.

[0011] Wherein, in step (1), the hydrothermal reaction is carried out at a temperature of 160 to 220° C. and a reaction time of 24 to 72 hours.

[0012] The step (1) is as follows: dissolving a bismuth source, a titanium source and an iron source in water respectively, stirring for 20 to 30 minutes to obtain a titanium source solution, an iron source solution and a bismuth source solution; sequentially adding the titanium source solution and the iron source solution to the bismuth source solution and stirring for 60 to 70 minutes, adjusting the pH to alkaline, stirring for 2 to 2.5 hours, performing a hydrothermal reaction, cooling, centrifuging, washing, and drying at 50 to 70° C. to obtain Bi5Ti3FeO 15 Nanosheets.

[0013] Wherein, in step (2), in step (2), the molar ratio of Bi to Br in the bismuth source and the bromine source is 1:1; the bismuth source is bismuth nitrate or bismuth acetate, the bromine source is KBr, 3-bromopyridine or hexadecyltrimethylammonium bromide, and the concentration of the bismuth source solution or the bromine source solution is 0.05 to 0.3 mol / L.

[0014] Specifically, step (2) comprises dissolving a bismuth source and a bromine source in water respectively, stirring to obtain a bismuth source solution and a bromine source solution; and adding the Bi5Ti3FeO 15 The nanosheets were added to water and stirred at room temperature for 30-40 min, bismuth source solution was added dropwise, stirred for 2-2.5 h, and then bromine source solution was added dropwise, stirred for 1-1.5 h, and then allowed to stand for 2-2.5 h, centrifuged, washed, and dried at 50-70 ° C to obtain two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst.

[0015] The present invention also discloses the above two-dimensional BiOBr / Bi5Ti3FeO 15 Application of composite piezoelectric photocatalysts in the degradation of organic dyes.

[0016] Among them, for the degradation of the organic dye, the composite piezoelectric photocatalyst generates a piezoelectric electric field and a photocatalytic effect under the action of light and ultrasound to synergistically degrade the organic dye. The frequency of the ultrasound is 10-60KHz, and the light source is a 100W xenon lamp.

[0017] Furthermore, mechanical energy such as water waves and sunlight are used to improve the degradation rate of organic dyes based on the piezoelectric effect and photocatalytic effect.

[0018] Invention principle: This invention firstly combines Bi5Ti3FeO with ferroelectric / piezoelectric properties 15 Nanosheets are composited with piezoelectric BiOBr nanosheets in Bi5Ti3FeO 15 BiOBr nanosheets are constructed in situ on the basis of nanosheets to form a composite piezoelectric heterojunction with a large contact surface and interface polarization, which improves the overall piezoelectric performance while improving the piezoelectric photocatalytic performance. 15 , it is easy to form a typical type II heterojunction, and the piezoelectric material BiOBr and the ferroelectric material Bi5Ti3FeO with spontaneous polarization 15 Under periodic external vibration and illumination conditions, the dual piezoelectric polarization electric field formed can effectively regulate the band structure of the heterojunction interface and effectively promote the migration and separation of photogenerated carriers.

[0019] BiOBr / Bi5Ti3FeO prepared by the method of the present invention 15 Composite piezoelectric photocatalytic materials can use the built-in electric field generated under ultrasonic cavitation to suppress the secondary recombination of photogenerated carriers, providing a strong and long-lasting internal driving force for the separation and migration of carriers. In addition, compared with other structures, two-dimensional nanosheets can produce greater deformation under the action of external mechanical forces, thereby generating a stronger polarization electric field. Moreover, two-dimensional materials have a large surface area and can form a heterojunction with close and large interface contact, effectively improving the transfer of photogenerated carriers. Therefore, the present invention uses BiOBr nanosheets and Bi5Ti3FeO 15 Two-dimensional BiOBr / Bi5Ti3FeO was prepared by nanosheet composite method. 15 Composite piezoelectric photocatalyst to improve its piezoelectric photocatalytic degradation performance of organic pollutants.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The piezoelectric photocatalyst of the present invention increases the area of ​​the composite interface through the structural characteristics of the two-dimensional heterojunction, thereby increasing the photogenerated carriers in BiOBr / Bi5Ti3FeO 15 The built-in electric field generated by ultrasonic cavitation inhibits the secondary recombination of photogenerated carriers, providing a strong and long-lasting intrinsic driving force for the separation and migration of carriers; (2) The raw materials of the preparation method are easy to obtain, the process is simple, and the operation is convenient, which is convenient for large-scale production; (3) Under the action of light and external ultrasound, the piezoelectric field and photocatalytic effect are generated to efficiently degrade organic dyes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The BiOBr / Bi5Ti3FeO synthesized in Example 1 of the present invention 15 Scanning electron microscopy image of the composite piezoelectric photocatalyst;

[0022] Figure 2 BiOBr / Bi5Ti3FeO prepared in the embodiment of the present invention 15 X-ray diffraction spectra of the composite piezoelectric photocatalyst and the materials prepared in the comparative example;

[0023] Figure 3 BiOBr / Bi5Ti3FeO prepared in the embodiment of the present invention 15 Comparison of the piezoelectric-photocatalytic degradation performance of Rhodamine B by the composite piezoelectric photocatalyst and the material prepared in the comparative example;

[0024] Figure 4 BiOBr / Bi5Ti3FeO prepared in the embodiment of the present invention 15 First-order kinetic fitting diagram of piezoelectric-photocatalytic degradation of Rhodamine B by the composite piezoelectric photocatalyst and the material prepared in the comparative example. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.

[0026] Example 1

[0027] The two-dimensional BiOBr / Bi5Ti3FeO of the present invention 15 The composite piezoelectric photocatalyst, the preparation method thereof comprises the following steps:

[0028] (1) Preparation of Bi5Ti3FeO by hydrothermal method 15 Nanosheets: Bismuth nitrate, tetrabutyl titanate and ferric nitrate with a molar ratio of Bi, Ti and Fe of 5:3:1 were dissolved in deionized water to concentrations of 0.5 mol / L, 0.3 mol / L and 0.1 mol / L, respectively, and stirred for 20 minutes. The tetrabutyl titanate solution and ferric nitrate solution were added to the bismuth nitrate solution in sequence and stirred for 60 minutes. A 3 mol / L ammonia solution was added to adjust the pH to 13, stirred for 2 hours, and placed in an oven for hydrothermal reaction at a temperature of 180°C for 48 hours. After natural cooling, centrifugation, washing and drying at 60°C were performed to obtain Bi5Ti3FeO 15 Nanosheets;

[0029] (2) Preparation of BiOBr / Bi5Ti3FeO by in situ chemical precipitation 15Nanosheet heterojunction: Dissolve bismuth nitrate and hexadecyltrimethylammonium bromide in deionized water at a molar ratio of 1:1, respectively, to a concentration of 0.05 mol / L. 15 Nanosheets were added to deionized water, BiOBr and Bi5Ti3FeO 15 The molar ratio of was 1:1, stirred at room temperature of 25°C for 30 minutes, bismuth nitrate solution was added dropwise, stirred for 2 hours, and then hexadecyltrimethylammonium bromide solution was added dropwise, stirred for 1 hour, and then allowed to stand for 2 hours, centrifuged, washed, and dried at 60°C to obtain BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst. Scanning electron microscope image Figure 1 As shown, the synthesized BiOBr / Bi5Ti3FeO 15 It exists in the form of nanosheet heterojunction.

[0030] Example 2

[0031] The two-dimensional BiOBr / Bi5Ti3FeO of the present invention 15 The composite piezoelectric photocatalyst, the preparation method thereof comprises the following steps:

[0032] (1) Preparation of Bi5Ti3FeO by hydrothermal method 15 Nanosheets: Bismuth acetate, TiCl4 and ferric nitrate with a molar ratio of Bi, Ti and Fe of 5:3:1 were dissolved in deionized water to concentrations of 0.5 mol / L, 0.3 mol / L and 0.1 mol / L, respectively, and stirred for 20 minutes. Tetrabutyl titanate solution and ferric nitrate solution were added to the bismuth nitrate solution in sequence, stirred for 60 minutes, and a 2 mol / L KOH solution was added to adjust the pH to 12, stirred for 2 hours, and placed in an oven for hydrothermal reaction, maintained at 220°C, and reacted for 36 hours. After natural cooling, centrifugation, washing, and drying at 60°C were performed to obtain Bi5Ti3FeO 15 Nanosheets;

[0033] (2) Preparation of BiOBr / Bi5Ti3FeO by in situ chemical precipitation 15 Nanosheet heterojunction: Dissolve bismuth nitrate and KBr in a molar ratio of 1:1 in deionized water to a concentration of 0.05 mol / L. 15 Nanosheets were added to deionized water, BiOBr and Bi5Ti3FeO 15 The molar ratio of was 1:1, stirred at room temperature of 25°C for 30 minutes, bismuth nitrate solution was added dropwise, stirred for 2 hours, and then KBr solution was added dropwise, stirred for 1 hour, and then allowed to stand for 2 hours, centrifuged, washed, and dried at 60°C to obtain BiOBr / Bi5Ti3FeO 15The composite piezoelectric photocatalyst is denoted as BOB@BTFONSs (1:1).

[0034] Example 3

[0035] The two-dimensional BiOBr / Bi5Ti3FeO of the present invention 15 The composite piezoelectric photocatalyst, the preparation method thereof comprises the following steps:

[0036] (1) Preparation of Bi5Ti3FeO by hydrothermal method 15 Nanosheets: Bismuth nitrate, tetrabutyl titanate and ferric nitrate with a molar ratio of Bi, Ti and Fe of 5:3:1 were dissolved in deionized water to concentrations of 0.5 mol / L, 0.3 mol / L and 0.1 mol / L, respectively, and stirred for 20 minutes. The tetrabutyl titanate solution and the ferric nitrate solution were added to the bismuth nitrate solution in sequence, stirred for 60 minutes, and a 1 mol / L NaOH solution was added to adjust the pH to 13, stirred for 2 hours, and placed in an oven for hydrothermal reaction, maintained at 200°C, and the reaction time was 48 hours. After natural cooling, centrifugation, washing, and drying at 60°C were performed to obtain Bi5Ti3FeO 15 Nanosheets;

[0037] (2) Preparation of BiOBr / Bi5Ti3FeO by in situ chemical precipitation 15 Nanosheet heterojunction: Dissolve bismuth nitrate and KBr with a molar ratio of Bi to Br of 1:1 in deionized water at a concentration of 0.1 mol / L, and mix the Bi5Ti3FeO obtained in step (1) 15 Nanosheets were added to deionized water, BiOBr and Bi5Ti3FeO 15 The molar ratio of was 1:2, stirred at room temperature of 25°C for 30 minutes, bismuth nitrate solution was added dropwise, stirred for 2 hours, and then KBr solution was added dropwise, stirred for 1 hour, and then allowed to stand for 2 hours, centrifuged, washed, and dried at 60°C to obtain BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst, denoted as BOB@BTFONSs(1:2).

[0038] Example 4

[0039] The two-dimensional BiOBr / Bi5Ti3FeO of the present invention 15 The composite piezoelectric photocatalyst, the preparation method thereof comprises the following steps:

[0040] (1) Preparation of Bi5Ti3FeO by hydrothermal method 15Nanosheets: Bismuth nitrate, tetrabutyl titanate and ferric nitrate with a molar ratio of Bi, Ti and Fe of 5:3:1 were dissolved in deionized water to concentrations of 0.5 mol / L, 0.3 mol / L and 0.1 mol / L, respectively, and stirred for 20 minutes. The tetrabutyl titanate solution and the ferric nitrate solution were added to the bismuth nitrate solution in sequence and stirred for 60 minutes. A 2 mol / L NaOH solution was added to adjust the pH to 10, stirred for 2 hours, and placed in an oven for hydrothermal reaction at a temperature of 220°C for 24 hours. After natural cooling, centrifugation, washing and drying at 60°C were performed to obtain Bi5Ti3FeO 15 Nanosheets;

[0041] (2) Preparation of BiOBr / Bi5Ti3FeO by in situ chemical precipitation 15 Nanosheet heterojunction: Dissolve bismuth nitrate and hexadecyltrimethylammonium bromide in deionized water at a molar ratio of 1:1, respectively, to a concentration of 0.03 mol / L, and mix the Bi5Ti3FeO obtained in step (1) 15 Nanosheets were added to deionized water, BiOBr and Bi5Ti3FeO 15 The molar ratio of was 1:3, stirred at room temperature of 25°C for 30 minutes, bismuth nitrate solution was added dropwise, stirred for 2 hours, and then hexadecyltrimethylammonium bromide solution was added dropwise, stirred for 1 hour, and then allowed to stand for 2 hours, centrifuged, washed, and dried at 60°C to obtain BiOBr / Bi5Ti3FeO 15 The composite piezoelectric photocatalyst is denoted as BOB@BTFONSs (1:3).

[0042] Comparative Example 1

[0043] Bi5Ti3FeO 15 Nanosheets, the preparation method thereof is as follows:

[0044] Bismuth nitrate, tetrabutyl titanate and ferric nitrate with a molar ratio of Bi, Ti and Fe of 5:3:1 were dissolved in deionized water to concentrations of 0.5 mol / L, 0.3 mol / L and 0.1 mol / L, respectively, and stirred for 20 minutes. Tetrabutyl titanate solution and ferric nitrate solution were added to the bismuth nitrate solution in sequence and stirred for 60 minutes. A 2 mol / L NaOH solution was added to adjust the pH to 10, stirred for 2 hours, and placed in an oven for hydrothermal reaction at a temperature of 220°C for 24 hours. After natural cooling, centrifugation, washing and drying at 60°C were performed to obtain Bi5Ti3FeO 15 Nanosheets.

[0045] Comparative Example 2

[0046] Mechanical mixing of BiOBr and Bi5Ti3FeO 15 Prepared mixed material:

[0047] Take BiOBr and Bi5Ti3FeO with a molar ratio of 1:2 15 , mix and grind at room temperature of 25°C for 20 minutes to obtain a mixed material.

[0048] The crystal phases of the materials obtained in Examples 2 to 4 and Comparative Example 1 were observed in the X-ray diffraction spectra. Figure 2 As shown, Bi5Ti3FeO 15 The diffraction peaks of BiOBr and Bi5Ti3FeO2 were respectively corresponding to their corresponding standard cards, confirming the successful synthesis of Bi5Ti3FeO2. 15 and BiOBr.

[0049] Figure 3 and Figure 4 The performance comparison diagrams and first-order kinetic fitting diagrams of the materials prepared in Examples 2 to 4 and Comparative Example 1 for degradation of Rhodamine B are shown respectively. Taking 25 mg / L RhB as the target pollutant, the degradation of BiOBr / Bi5Ti3FeO with different molar ratios was evaluated under the illumination conditions of a 100W xenon lamp light source and an ultrasonic condition with a frequency of 10-60KHz. 15 The piezoelectric photocatalytic properties of the composites, e.g. Figure 3 As shown, with Bi5Ti3FeO 15 In comparison, the BiOBr / Bi5Ti3FeO 15 The composite piezoelectric photocatalyst can effectively enhance the piezoelectric photocatalytic performance. 15 The best performance was achieved when the molar ratio was 1:2, and the complete degradation of RhB dye was achieved within 6 minutes, and the calculated reaction rate was 0.53996min -1 , much larger than Bi5Ti3FeO 15 and mechanical mixing performance.

Claims

1. A two-dimensional BiOBr / Bi5Ti3FeO 15 A composite piezoelectric photocatalyst, characterized in that The composite piezoelectric photocatalyst is BiOBr nanosheets on Bi5Ti3FeO 15 The two-dimensional heterojunction nanosheet material is formed by in-situ growth of nanosheets, in which BiOBr and Bi5Ti3FeO 15 The molar ratio of RhB is 3:1 to 1:3; taking 25 mg / LRhB as the target pollutant, under the illumination condition of a 100W xenon lamp light source and an ultrasonic condition of a frequency of 10-60KHz, the RhB dye is completely degraded within 6 minutes; the photocatalyst is prepared by the following steps: (1) Dissolving a bismuth source, a titanium source and an iron source in water respectively, and stirring to obtain a titanium source solution, an iron source solution and a bismuth source solution; adding the titanium source solution and the iron source solution to the bismuth source solution in sequence, stirring, adjusting the pH to alkaline, stirring, performing a hydrothermal reaction, cooling, centrifuging, washing and drying, and obtaining Bi5Ti3FeO 15 Nanosheets; (2) dissolving a bismuth source and a bromine source in water respectively, stirring to obtain a bismuth source solution and a bromine source solution; adding the Bi5Ti3FeO 15 The nanosheets were added to the water and stirred, and the bismuth source solution was added dropwise. After stirring, the bromine source solution was added dropwise. After stirring, the mixture was allowed to stand, centrifuged, washed, and dried to obtain the two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst.

2. The composite piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), the bismuth source is bismuth nitrate or bismuth acetate, the titanium source is tetrabutyl titanate or TiCl4, and the iron source is Fe(NO3)3·9H2O; the concentration of the bismuth source solution, the titanium source solution or the iron source solution is 0.1-0.5 mol / L.

3. The composite piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), an alkaline solution is used to adjust the pH to 10-13, and the alkaline solution is one of NaOH, KOH or ammonia solution, and the concentration is 0.5-2 mol / L.

4. The composite piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), the hydrothermal reaction is carried out at a temperature of 160 to 220° C. and a reaction time of 24 to 72 hours.

5. The composite piezoelectric photocatalyst according to claim 1, characterized in that: Step (1) is specifically as follows: dissolving a bismuth source, a titanium source and an iron source in water respectively, stirring for 20 to 30 minutes to obtain a titanium source solution, an iron source solution and a bismuth source solution; sequentially adding the titanium source solution and the iron source solution to the bismuth source solution and stirring for 60 to 70 minutes, adjusting the pH to alkaline, stirring for 2 to 2.5 hours, performing a hydrothermal reaction, cooling and centrifuging, washing, and drying at 50 to 70° C. to obtain Bi5Ti3FeO 15 Nanosheets.

6. The composite piezoelectric photocatalyst according to claim 1, characterized in that: In step (2), the bismuth source is bismuth nitrate or bismuth acetate, the bromine source is KBr, 3-bromopyridine or hexadecyltrimethylammonium bromide, and the concentration of the bismuth source solution or the bromine source solution is 0.05 to 0.3 mol / L.

7. The composite piezoelectric photocatalyst according to claim 1, characterized in that: Step (2) specifically comprises dissolving a bismuth source and a bromine source in water respectively, stirring to obtain a bismuth source solution and a bromine source solution; and mixing the Bi5Ti3FeO 15 The nanosheets were added to water and stirred at room temperature for 30-40 min, bismuth source solution was added dropwise, stirred for 2-2.5 h, and then bromine source solution was added dropwise, stirred for 1-1.5 h, and then allowed to stand for 2-2.5 h, centrifuged, washed, and dried at 50-70 ° C to obtain two-dimensional BiOBr / Bi5Ti3FeO 15 Composite piezoelectric photocatalyst.

8. A two-dimensional BiOBr / Bi5Ti3FeO as claimed in claim 1 15 Application of composite piezoelectric photocatalysts in the degradation of organic dyes.

9. The use according to claim 8, characterized in that: For the degradation of the organic dye, the composite piezoelectric photocatalyst generates a piezoelectric electric field and a photocatalytic effect under the action of light and ultrasound to synergistically degrade the organic dye, and the frequency of the ultrasound is 10-60 KHz.

Citation Information

Patent Citations

  • Bismuth oxychloride-iron bismuth titanate composite photocatalyst and preparation method thereof

    CN104511293A

  • Cobalt tungstate / bismuth / bismuth oxybromide ternary heterojunction composite material and preparation method and application thereof

    CN113509942A

  • Preparation method of BiVO4-based piezoelectric electro-catalytic composite nanomaterial

    CN115814782A